Physical Mapping of Peroxidase Genes and Development of Functional Markers for TaPod-D1 on Bread Wheat Chromosome 7D - Geng, Hongwei; Shi, Jia; Fuerst, E. Patrick; Wei, Jingxin; Morris, Craig F. (Frontiers in Plant Science, 2019)
Peroxidase (POD) activity in grain is an important factor determining the color of ﬂour and end-use products of wheat. Here, we report the molecular characterization and physical mapping of POD genes in common wheat (Triticum aestivum L.). The full-length genomic DNA (gDNA) sequence of two POD genes (TaPod-A2 and TaPod-D1), and the partial gDNA sequence of two POD genes (TaPod-A3 and TaPod-B1) from common wheat were characterized by in silico cloning and experimental validation. Using a set of nullisomic-tetrasomic (NT) lines, six group 7 ditelosomic lines and 38 group 7 deletion lines of Chinese Spring, TaPod-A2 and TaPod-D1 were found to be physically located on 0.73-0.83 and on the most distal 0.39 fraction arm length of chromosomes 7AS and 7DS in cv. Chinese Spring, respectively; whereas, TaPod-A3 and TaPod-B1 were assigned to the 0.40-0.49 and 0.40-0.48 fraction arm length of chromosomes 7AL and 7BL, respectively. Two complementary dominant sequence tagged site (STS) markers, POD-7D6 and POD-7D1, were developed based on single nucleotide polymorphisms (SNPs) of two alleles at the TaPod-D1 locus, amplifying 640- and 540-bp fragments in cultivars with lower and higher POD activities, respectively. POD-7D1 and POD-7D6 were validated on 224 Chinese wheat cultivars and advanced lines and showed highly significant (p < 0.01) associations with POD activity. Our work provides new information on the POD genes in common wheat, insight into wheat genome synteny and structure, gene-specific markers, and contributes a valuable resource for wheat quality improvement and breeding.